2004
DOI: 10.1073/pnas.0405266101
|View full text |Cite
|
Sign up to set email alerts
|

CD26 up-regulates expression of CD86 on antigen-presenting cells by means of caveolin-1

Abstract: CD26 is a T cell costimulatory molecule with dipeptidyl peptidase IV activity in its extracellular region. We previously reported that recombinant soluble CD26 enhanced T cell proliferation induced by the recall antigen tetanus toxoid (TT). However, the mechanism involved in this enhancement is not yet elucidated. We now demonstrate that CD26 binds Caveolin-1 on antigen-presenting cells, and that residues 201-211 of CD26 along with the serine catalytic site at residue 630 contribute to binding to caveolin-1 sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
140
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(145 citation statements)
references
References 46 publications
5
140
0
Order By: Relevance
“…Moreover, we showed that residues 201-211 of CD26 along with the serine catalytic site at residue 630, which constitute a pocket structure of CD26/DP-PIV, contribute to binding to caveolin-1 scaffolding domain (14). More recently, we demonstrated that caveolin-1 binds to Tollip (Toll-interacting protein) and IRAK-1 (interleukin-1 receptor associated serine/threonine kinase 1) in the membrane of tetanus toxoid-loaded monocytes, and following exogenous CD26 stimulation, Tollip and IRAK-1 disengage from caveolin-1, with IRAK-1 being subsequently phosphorylated to up-regulate CD86 expression (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we showed that residues 201-211 of CD26 along with the serine catalytic site at residue 630, which constitute a pocket structure of CD26/DP-PIV, contribute to binding to caveolin-1 scaffolding domain (14). More recently, we demonstrated that caveolin-1 binds to Tollip (Toll-interacting protein) and IRAK-1 (interleukin-1 receptor associated serine/threonine kinase 1) in the membrane of tetanus toxoid-loaded monocytes, and following exogenous CD26 stimulation, Tollip and IRAK-1 disengage from caveolin-1, with IRAK-1 being subsequently phosphorylated to up-regulate CD86 expression (15).…”
mentioning
confidence: 99%
“…In our previous study (14), we identified caveolin-1 in antigen-presenting cells (APC) as a binding protein for CD26, and we demonstrated that CD26 on activated memory T-cells directly faces caveolin-1 on tetanus toxoid-loaded monocytes in the contact area, which was revealed as the immunological synapse for T-cell-APC interaction. Moreover, we showed that residues 201-211 of CD26 along with the serine catalytic site at residue 630, which constitute a pocket structure of CD26/DP-PIV, contribute to binding to caveolin-1 scaffolding domain (14).…”
mentioning
confidence: 99%
“…Caveolin-1 is a ubiquitously expressed ligand of CD26 in many cell types such as epithelial cells, endothelial cells, fibroblasts, macrophages, and neutrophils. We have previously shown that caveolin-1 was detected on the cell surface of monocytes 12-24 h after Ag uptake, and that CD26 and caveolin-1 colocalized at the T cell/ monocyte contact site (19). Moreover, caveolin-1 expression is regulated by NF-kB, and stimulation with LPS or TNF-a increases the expression of caveolin-1 mRNA and protein (54), suggesting that expression of caveolin-1 may be increased on cells accumulated at sites of inflammation, leading to the transduction of intensive CD26-mediated signaling in CD26 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…siRNAs against EGR2 were purchased from Sigma-Aldrich, and negative control siRNA (oligonucleotide sequences are not disclosed) was purchased from Qiagen (Valencia, CA). Fifty picomoles siRNA duplexes were transfected into 5 3 10 5 purified CD4 + T cells by using HVJ-E vector (GenomONE-Si; Ishihara Sangyo Kaisha, Osaka, Japan) according to the manufacturer's instructions (19,20).…”
Section: Small Interfering Rna Against Human Egr2mentioning
confidence: 99%
See 1 more Smart Citation